2022
DOI: 10.3390/ceramics5040060
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Durability Performance of Lightweight Fly Ash Based Geopolymer Composites Incorporating Expanded Polystyrene and Expanded Perlite

Abstract: In this study, the use of expanded polystyrene and expanded perlite as lightweight aggregates for the preparation of lightweight geopolymers is tested. The geopolymers’ performance was evaluated through physical, mechanical and thermal testing. Polypropylene fibers were used as reinforcement agents, while the long-term durability was assessed though repeated wet–dry and freeze–thaw cycles and sorptivity tests. The results showed that the introduction of lightweight aggregates in the geopolymer mixes decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…On the other side, cement and construction composites have great interest due to the different applications and benefits they provide. One of the recycling methods is the use of polymer waste, solid byproducts, natural waste, and bricks in construction materials, such as composite blocks and lightweight partitions, to share with the waste management. Several features, such as lightweight, high strength and elasticity, easy processing, corrosion resistance, low cost, and weathering resistance, make them alternatives to commercial aggregates in modern building and low-density construction applications. Composites are included in different forms and types due to the durability and improved properties, such as reinforced concrete, reinforced plastic, cement, polymer–cement composite, fiber–cement composite, and fiber–polymer composite. , The global consumption of plastic in the building and construction markets is expected to be duplicated in 2027 with more intense studies. The influence of adding waste powders of concrete bricks and recycled polyethylene terephthalate on mortar was studied in novel improved construction composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other side, cement and construction composites have great interest due to the different applications and benefits they provide. One of the recycling methods is the use of polymer waste, solid byproducts, natural waste, and bricks in construction materials, such as composite blocks and lightweight partitions, to share with the waste management. Several features, such as lightweight, high strength and elasticity, easy processing, corrosion resistance, low cost, and weathering resistance, make them alternatives to commercial aggregates in modern building and low-density construction applications. Composites are included in different forms and types due to the durability and improved properties, such as reinforced concrete, reinforced plastic, cement, polymer–cement composite, fiber–cement composite, and fiber–polymer composite. , The global consumption of plastic in the building and construction markets is expected to be duplicated in 2027 with more intense studies. The influence of adding waste powders of concrete bricks and recycled polyethylene terephthalate on mortar was studied in novel improved construction composites.…”
Section: Introductionmentioning
confidence: 99%
“…One of the recycling methods is the use of polymer waste, solid byproducts, natural waste, and bricks in construction materials, such as composite blocks and lightweight partitions, to share with the waste management. 22 24 Several features, such as lightweight, high strength and elasticity, easy processing, corrosion resistance, low cost, and weathering resistance, make them alternatives to commercial aggregates in modern building and low-density construction applications. 25 28 Composites are included in different forms and types due to the durability and improved properties, such as reinforced concrete, reinforced plastic, cement, polymer–cement composite, fiber–cement composite, and fiber–polymer composite.…”
Section: Introductionmentioning
confidence: 99%
“…At an average temperature of 25 °C, it was found that the thermal conductivity of common polymers such as HDPE, LDPE, and PP is 0.43 W/mK, 0.35 W/mK, and 0.23 W/mK, respectively, which is three to thirteen times lower than the typical thermal conductivity of ordinary concretes ranging from 1.34-2.92 W/mK [63]. In the study of Kioupis et al [64], 0.5%, 1%, 1.5%, 2%, 2.5%, and 3% of EPS plastics were added, resulting in a significant reduction of up to 40% (at maximum EPS content of 3%) in the thermal conductivity of the fly ash-based geopolymer. On the other hand, Bahij et al [65] achieved 6.6%, 12.1%, and 15.5% reductions with 0.25%, 0.50%, and 0.75% non-woven PET addition to the concrete mixtures.…”
Section: Thermal Conductivitymentioning
confidence: 95%
“…They are highly suitable as latent hydraulic or pozzolanic additives in cement and/or concrete but their availability will diminish by policy changes related to green transition such as switching from coal power plants to renewable energy sources and changing steel production into hydrogen reduction and electric arc furnaces. The availability of suitable precursor materials can be a critical factor in the successful implementation of the alkali‐activation technology; hence, there is an ongoing search for alternative precursors and activators which includes various mine tailing slags, red mud, biomass ashes, construction and demolition waste, calcined clays, and more 50–60 . The valorization of widely available, aluminosilicate‐containing mine tailings to make geopolymers is also a rich area of potential research.…”
Section: What Are the Barriers?mentioning
confidence: 99%